Development of an ultrasonic medical imaging system using diffraction tomography and acoustical fractal imaging - Er, Meng Joo (2008)
Breast cancer is known as one of the most commonly contracted cancers among women today. Since the actual cause or cure of breast cancer is still under research, the best solution available is early detection through screening. Recent studies have shown that although several screening methods are available, namely Mammography (x-ray imaging), Magnetic Resonance Imaging (MRI) and Ultrasound Tomography (UT), the detection of tumour is not sufficient enough to determine whether certain cells will develop into breast cancers. Instead, a more important factor that will determine the malignancy of a cell is its rate of growth. One way of determining the rate is by having more frequent screenings. This research discusses methods employed in tackling the major drawback faced in UT, which is a form of diffraction tomography, since the effects of diffraction are considered. The various aspects of diffraction tomography and two main methods used for solving an inverse problem are first presented to illustrate the deficiencies of current methods.